Dogma and Legal History in Russian Science of Civil Law - Dmitry Poldnikov (Journal on European History of Law)
The paper presents the analysis of correlation between the legal dogma and legal history as it was reflected in the theoretical publications of several renowned Russian Private Law scholars throughout the 20th century. The author states that historical argument may, and should, perform the explanatory and corrective functions in relation to legal dogma, but de facto it serves as an ornament in Russian Private Law studies. The author traces the causes of this discrepancy between the desired and actual state of the legal discipline by examining colloquial, philosophical and legal meanings of “dogma” in Russia; European ancient and medieval origins of the legal dogma; and its link with the modern Roman law. The author argues in favour of a more active usage of Legal History in order to correct the inherent drawbacks of dogmatic approach to legal research.